The contribution of Muslim scholars in comparative religion: Selected writings - Shehu, Fatmir Mehdi (2017)
This Text Book is designed to introduce the reader (students) to the contribution of Muslim scholars in comparative religion through their selected writings. Firstly, Qur’an and Prophetic Sunnah will be studied as essential foundations addressing the right methodology for the science of comparative religion. Muslim scholars have been inspired by the Quranic methodology and Prophetic way concerning their writings on other religions. Secondly, the history and development of the discipline of comparative study of other religions from both, Muslim scholars and Western scholars will be briefly discussed in a comparative way. Thirdly, methodologies of selected Muslim scholars employed in the study of other religions will be examined and analysed in light of a proper classification: (1) Documentary Approach – Ibn Nadim and Shahrastani; (2) Travelogue Approach: Ibn Batuta; (3) Polemical, Refutative and Analytical Approach(s): Isa al-Warraq, Ibn Hazm, and Ibn Taymiyyah; (4) Comparative, Descriptive and Objective Approach(s): Al-Biruni, Al-Faruqi and Al-Fattah. The contribution of each Muslim scholar will be discussed as follow: (1) Scholar’s Chronology, (2) his selected work(s), (3) methodology, and (4) analysis of selected texts from his writings in the original language in order to reveal the methods employed by him in the study of other religion(s).